Evidence for the role of sound on the growth and signal response in duckweed. (31st December 2023) - Ye, Zi; Yang, Rui; Xue, Ying; Xu, Ziyi; He, Yuman; Chen, Xinglin; Ren, Qiuting; Sun, Jinge; Ma, Xu; Hu, Jerri; Yang, Lin
ABSTRACT: Sound vibration, an external mechanical force, has been proven to modulate plant growth and development like rain, wind, and vibration. However, the role of sound on plants, especially on signal response, has been usually neglected in research. Herein, we investigated the growth state, gene expression, and signal response in duckweed treated with soft music. The protein content in duckweed after music treatment for 7 days was about 1.6 times that in duckweed without music treatment. Additionally, the potential maximum photochemical efficiency of photosystem II (Fv/Fm) ratio in duckweed treated with music was 0.78, which was significantly higher in comparison with the control group (P < .01). Interestingly, music promoted the Glu and Ca signaling response. To further explore the global molecular mechanism, we performed transcriptome analysis and the library preparations were sequenced on an Illumina Hiseq platform. A total of 1296 differentially expressed genes (DEGs) were found for all these investigated genes in duckweed treated with music compared to the control group. Among these, up-regulation of the expression of metabolism-related genes related to glycolysis, cell wall biosynthesis, oxidative phosphorylation, and pentose phosphate pathways were found. Overall, these results provided a molecular basis to music-triggered signal response, transcriptomic, and growth changes in duckweed, which also highlighted the potential of music as an environmentally friendly stimulus to promote improved protein production in duckweed.